Associations between sexual and reproductive health knowledge, attitude and practice of partners and the occurrence of unintended pregnancy - Liu, Ruping; Dong, Xiaotong; Ji, Xiaoning; Chen, Shihan; Yuan, Qingqing; Tao, Yi; Zhu, Yaping; Wu, Sufang; Zhu, Jingfen; Yang, Yongbin (Frontiers in Public Health, 2023)
Background Although global contraceptive coverage has increased significantly, high rates of unintended pregnancy remain the current global status quo. A comparative analysis of the differences and correlations of knowledge, attitude and practice (KAP) of sexual and reproductive health (SRH) of both partners will help guide public health work according to gender characteristics and needs, and reduce the occurrence of unintended pregnancy. Methods A questionnaire survey of people with unintended pregnancies including women and their male partners (n = 1,275 pairs) who sought help from the Shanghai General Hospital Affiliated to Shanghai Jiao Tong University School of Medicine from October 2017 to October 2021. Data were collected on sexual and reproductive health knowledge, attitudes, and practices in both partners who had unintended pregnancies. Chi-square test and Logistic regression were used to analyze the relationship between the occurrence of unintended pregnancy and KAP and its influencing factors. Paired odds ratio and McNemar's test were used to estimate the difference and concordance of KAP between partners. Results This study included 1,275 partners with a mean age of 30.0 years. The partner's overall level of KAP is good. Compared with women, men had better knowledge (χ2 = 3.93, p = 0.047) and more active contraceptive practices (χ2 = 19.44, p < 0.001). In the analysis of partner concordance, male contraceptive intention was found to be better than female [matched pairs odds ratio (ORMP) = 2.56, p < 0.001], and the concordance of positive contraceptive practice between partners increased with male education [adjusted odds ratio (aOR) = 1.556, 95% confidence interval (CI) = 1.185–2.044, p = 0.001]. In partner-paired regression analysis, compared with good contraceptive knowledge in both men and women in the partner, the risk of negative contraceptive practice was 1.7 times (aOR = 1.721, 95% CI = 1.234–2.400, p = 0.001) higher with good contraceptive knowledge in women but negative in men, while women with poor contraceptive knowledge but men with good knowledge are 1.3 times (aOR = 1.349, 95% CI = 1.000–1.819, p = 0.05) more likely to have negative contraceptive practices. In addition, compared with partners with positive contraceptive attitudes, women with positive attitudes but negative men and women with negative attitudes but positive men had 1.7 and 1.4 times the risk of negative contraceptive practices, respectively. Conclusion The study found that unintended pregnancy occurs mainly in young people, and the younger age of first sexual intercourse, the low education background and the lack of discussion of contraception between partners are risk factors for not taking contraceptive measures. Men's better knowledge and contraceptive practices compared with female partners, and poor male contraceptive knowledge and attitudes may lead to a higher risk of negative contraceptive practices, the results suggest that male KAP plays an important role in promoting contraceptive use and reducing unintended pregnancy.